Influência da saliidade e da disponibilidade de nutrientes no crescimento inicial de Canavalia rosea (Sw.) DC e de Passiflora mucronata Lam em um trecho de restinga - Lourenço Júnior, Jehová (2007)
In the coastal plain vegetation (restinga) of Paulo Cezar Vinha State Park in Guarapari-ES, there are 12 restinga vegetation types or zones with very distinct physiognomies, following a species distribution and diversity gradient toward the continent interior. Thus, Canavalia rosea (Fabaceae) is restricted on creeping psammophytic zone, whereas Passiflora mucronata (Passifloraceae) is located on Palm scrub zone. There are several hypotheses about the vegetation zones stand, and the most outspread one is the saline gradient. Recently, the soil fertility factor has been also postulated. Trying to elucidate these questions, it was carried out the present study in order to investigate the salinity and mineral nutrition influence on the C. rosea and P. mucronata initial growth. Both species were grown with restinga soil in witch it was applied NaCl saline solution of 0, 200, 400 e 600mM. In nutritional experiment, the plants were grown in washed sand where it was applied weekly the Hoagland & Arnon (1936) nutritive solution at 20, 100 and 200% of ionic strength. The experiments were performed in a green house with natural light, temperature, and photoperiod. With the dry matter and leaf area data it was calculated the relative growth ratio (RGR), the net assimilation ratio (NAR), the leaf area ratio (LAR), the root/shoot ratio (RS), and the biomass allocation (root, stem and leaf fraction mass) according to Hunt (1982). It was also performed chemical and physical soil analyses of Creeping psammophytic and Palm scrub zone. The results showed that, on the whole, the increase of salinity affected both species growth. Both plants did not survive the highest levels of salinity (400 and 600mM), and C. rosea was later affected. The best performance was by the C. rosea plants growing in 0mM NaCl solution, whict reveled better biomass production. The C. rosea R:S ratio decreased in higher salinity levels, on the other hand, opposite effect was verified for P. mucronata plants. The soil analyses reveled that the sodium concentration was equivalent in both vegetations zones analyzed, and significant differences occurred as to the soil fertility. The Palm scrub vegetation develops on soils with higher organic matter and bases saturation values. This information confirms those results from the growth analysis, because P. mucronata plants have better growth (higher RGR and NAR) with the increase of nutrient availability, whereas C. rosea plants have a superior development in low ionic strength solution. The results allow-us to conclude that the fertility gradient must be a preponderant factor in the plant position of the vegetal zones studied at the restinga of Paulo Cezar Vinha State Park.